VEGETATION DYNAMICS ISLAND SEAL WHEN THE LEVEL FLUCTUATIONS OF THE CASPIAN SEA - Z. I. Soltanmuradova; A. A. Teimurov (Юг России: экология, развитие)
Aim. The study of the vegetation of the island seal under the influence transgressive-regressive fluctuations of the Caspian sea Methods. Collection of field data was carried out routing and forwarding method. To collect and herborization plants used by traditional equipment necessary for floral studies. When identifying plants in laboratory conditions used stereomicroscope MBS-2 and field telescopes with 8-fold magnification. Results. As a result of changes of the Caspian sea level is the transformation of the vegetation and soils of the Islands. During the transgressive cycle of development is shifting xerophytes halophytes and hydrophytes, automorphous soils hydromorphic. During the regressive cycle develops a reverse trend. Main conclusions. Succession from sagebrush-solenkovoy vegetation to wormwood, and then to sagebrush-grass or grass-sagebrush are amid higher hypsometric level and reduce the salinity of the soil substrates